PEMBATALAN PERJANJIAN JUAL BELI HAK ATAS TANAH AKIBAT ADANYA UNSUR KHILAF - Fajaruddin Fajaruddin (Universitas Muhammadiyah Sumatera Utara, 2017)
The occurrence of wanprestasi in an engagement as a source of sale and purchase agreement that always begins with contractual relationships (characteristics of default is always preceded by a contractual relationship) can be caused by some elements of which one of the elements is err. As a result of the law, the land purchase agreement which is made contains elements of khilaf reflected in Article 1321 and 1449 Civil Code. Article 1321 Civil Code: Affirms: “There is no legitimate agreement if the agreement is given by mistake, or obtained by coercion or fraud”, and Article 1449 of the Civil Code states: “A contract made by force, an oversight or a fraud, publishes a demand to annul it”.